Banking in the early stages of industrialization: a study in comparative economic history - Cameron, Rondo E. (New York: Oxford University Press, 1967)
The primary purpose of this volume is to shed light on a pressing practical problem-namely,financing economic development
Bibliography: p. 322-336.
obn 24/01/2019
Loans
Keywords: Industrialization; Banks and banking; Economic history